Revision of AUDIT Consumption Items to Improve the Screening of Youth Binge Drinking - Cortés-Tomás, María-Teresa; Giménez-Costa, José-Antonio; Motos-Sellés, Patricia; Sancerni-Beitia, María-Dolores (Frontiers in Psychology, 2017)
This study analyzes the appropriateness of an improved version of one of the most frequently used instruments for the screening of high-risk alcohol consumption. This adaptation was created in accordance with certain limitations recognized by other researchers and in an attempt to adjust the content and scales of some items to a more consensual definition of Binge Drinking. After revising items 2 and 3, the areas under the ROC curves of the AUDIT and of different abbreviated versions were calculated. A total of 906 minors (468 female) between the ages of 15 and 17 were evaluated. Stratified sampling was conducted on a population of high school students in the city of Valencia (Spain). One school was randomly chosen from each of the city’s 16 school districts. Information was collected on sociodemographic aspects, consumption patterns and the AUDIT containing the improved items. The percentage of underage BD reached 36%, regardless of gender or age. BD groups have been differentiated by different intensity levels, both in males and females. Upon comparing the effectiveness of the distinct versions of the AUDIT, it is recommended that researchers and clinics use the combination of the revised items 2 and 3 to ensure a more precise identification of underage BD. A cut-off point of 5 for this test would permit identification of 94% of the underage BD and would notably reduce false positives.